2020
DOI: 10.1016/j.healthplace.2019.102254
|View full text |Cite
|
Sign up to set email alerts
|

Finding common ground: The conception of community arts festivals as spaces for placemaking

Abstract: The present research posits the significant role that arts and cultural festivals play in contributing to placemaking and generating well-being within communities. Placemaking is recognized to be important when considering how to improve population health and wellbeing, and festivals can be seen to amplify those benefits. Drawing on qualitative data gathered from interviews with festival organizers in SouthEast England and deploying theories of space from Foucault and Massey, the present article argues that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Qualitative research is considered highly useful in examining complex and subjective issues associated with a research problem (Braun & Clarke, 2014) and helps the researcher to gain insights into how individuals create meanings (Patton, 2015;Flick, 2009). Cultural festivals are suggested as a complex phenomenon (Lau & Li, 2015), integrated sites (Perry et al, 2020) which are multifaceted, dynamic in nature, and involve intricate interactions among space, people, and affect (Brownett & Evans, 2020). Therefore, taking into account the multiple constituents of the context, the study demanded the compilation of different types of data to reach logical conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research is considered highly useful in examining complex and subjective issues associated with a research problem (Braun & Clarke, 2014) and helps the researcher to gain insights into how individuals create meanings (Patton, 2015;Flick, 2009). Cultural festivals are suggested as a complex phenomenon (Lau & Li, 2015), integrated sites (Perry et al, 2020) which are multifaceted, dynamic in nature, and involve intricate interactions among space, people, and affect (Brownett & Evans, 2020). Therefore, taking into account the multiple constituents of the context, the study demanded the compilation of different types of data to reach logical conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Collective control over decision-making has also been suggested as a means whereby community members can influence processes that determine their health and wellbeing ( Whitehead et al, 2016 ). Brownett and Evans (2020) have suggested that local events such as community festivals can instil a connection and sense of belonging to places, with positive effects on public health. Area reputation has been linked to health positively ( McKenzie, 2012 ; Popay et al, 2003 ) and negatively ( Thomas, 2016 ).…”
Section: Place and Health: A Typologymentioning
confidence: 99%
“…Community cultural festivals have recently been posited as significant generators of wellbeing benefits (Brownett 2018;Brownett and Evans 2020) for the way they bring local people together to celebrate arts and culture, finding common ground often outside the 'temples of culture' (Larson 1997). This selfsame role can, and will, be played by community-led cinema in the future, especially if the pandemic has laid waste to what some might see as the 'elite' cultural venues such as theatres and galleries, whose futures remain very uncertain.…”
mentioning
confidence: 99%